Suspension high velocity oxy fuel thermal spraying for biomedical coatings - Bano, Saira (2021)
Thermal spraying of bioglasses offers the opportunity to produce coatings for different biomedical applications. The resorption of the coatings can be adjusted by tailoring the chemical composition of the glass and the coating microstructure.